2019
DOI: 10.1128/msphere.00173-19
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infects Trabecular Meshwork and Causes Trabeculitis and Glaucomatous Pathology in Mouse Eyes

Abstract: Zika virus (ZIKV) infection during pregnancy leads to devastating fetal outcomes, including neurological (microcephaly) and ocular pathologies such as retinal lesions, optic nerve abnormalities, chorioretinal atrophy, and congenital glaucoma. Only clinical case reports have linked ZIKV infection to causing glaucoma, a major blinding eye disease. In the present study, we have investigated the role of ZIKV in glaucoma pathophysiology using in vitro and in vivo experimental models. We showed that human primary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 69 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…TLRs have been shown to play a key role in the initiation of innate immune defense in the retina following bacterial and viral infection and TLR deficiency makes mice more susceptible to disease [26,27,28,40,44,45,46,47,48]. Several fungal ligands have been shown to interact with various TLRs, e.g., fungal chitin directly binds to TLR2 and induce an inflammatory response [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLRs have been shown to play a key role in the initiation of innate immune defense in the retina following bacterial and viral infection and TLR deficiency makes mice more susceptible to disease [26,27,28,40,44,45,46,47,48]. Several fungal ligands have been shown to interact with various TLRs, e.g., fungal chitin directly binds to TLR2 and induce an inflammatory response [49].…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was performed on retinal cryosections following Aspergillus infection as described in our recent publications [27,28]. Briefly, infected and control mice eyes were enucleated and fixed in 4% PFA, dehydrated, and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the adjustment of intraocular pressure is particularly important for the treatment of glaucoma. As noted above, the primary cilia of the trabecular meshwork shorten in response to fluid flow and elevated aqueous humor pressure ( Singh et al., 2019 ). Lowe syndrome is an X-linked congenital disease that has glaucoma as one of its typical manifestations.…”
Section: Primary Cilia Of Ocular Tissuesmentioning
confidence: 99%
“…64 Our results are similar to those reported in C57BL/6 mice that developed retinal and corneal pathology, such as retinal edema and hyperplasia, following ZIKV infection. 56,65 Manangeeswaran et al found that retinal lesions and ocular pathology persists in C57BL/6 up to 90 days and correlates with elevated cytokine levels, but was performed in suckling neonatal mice. 66 Our data in the BALB/c model agree with the findings in C57BL/6 mice, and expand in the field of ZIKV neuro-ocular pathology and the underlying mechanisms, providing further insight into current knowledge gaps.…”
Section: Discussionmentioning
confidence: 99%